An Uncommon Presentation of Multiple Myeloma - Singha, Chayan Kumar; Biswas, Eshita; Islam, Md. Tanvir; Jahan, Ferdous; Chowdhury, MA Jalil; Sarker, Zilan Miah (Journal of Medicine, 2014)
Multiple myeloma can sometimes manifest only with fracture. We report the case of an individual who presented with a progressive right sided localized hip pain that made him difficulty in walking and also significant weight loss. Investigations revealed anaemia with markedly raised ESR, fracture in the right neck of the femur, monoclonal gamopathy on protein electrophoresis and 70% atypical plasma cells in the bone marrow. Subsequently he was managed in haematology and radiotherapy department accordingly. DOI: http://dx.doi.org/10.3329/jom.v14i2.19673 J Medicine 2013, 14(2): 189-191